390 DEPENDENCY OF ENDOTHELIAL NITRIC OXIDE SYNTHASE-ACTIVATION MECHANISMS ON INTRACELLULAR CA2+-CONCENTRATION IN HUMAN ATRIAL MYOCARDIUM. (1st January 2005) - Pott, C.; Bloch, W.; Steinritz, D.; Brixius, K.; Mehlhorn, U.; Ziskoven, C.; Schwinger, R. H.G.
Abstract : We have recently shown two ways of endothelial nitric oxide synthase (eNOS)-activation in human myocardium (Brixius et al. 2004): 1) a translocation and 2) an Akt-dependent phosphorylation of the enzyme at Ser1177. The present study investigates the Ca2+ dependency of these two mechanisms. Methods and Results: Human right atrial tissue was obtained from patients undergoing coronary bypass-operation. In immunohistochemical experiments, the translocated form of eNOS as well as the (Ser1177)-phosphorylated eNOS (peNOS) and the phosphorylated form of Akt (pAkt) were labelled using specific antibodies. eNOS-translocation was measured in the absence and presence of the Ca2+ chelator BAPTA after application of BRL 37344 (BRL), a preferential β3-adrenoceptor agonist, which has been shown to increase eNOS activity in human right atrial myocardium. In the absence of BAPTA, BRL (10 μM) time-dependently increased staining intensity of translocated eNOS (+BRL, t=5 min, +53.52±15.21%; n=6; p≤0.05), whereas in the presence of BAPTA, this effect was blunted (20 μM; +BRL (10 μM; t=5 min): -42.11±11.26%; n=4; p(0.05). In contrast, BRL 37344 significantly increased staining of peNOS (+BRL 37344 (10 μM; t=5 min): +156.6±26.4%; n=3; p≤0.05) and pAkt in the presence of BAPTA. Using the NO-sensitive dye diaminofluorescein (DAF), we could show that BRL induced a strong release of NO (+BRL 37344 (10 μM): +237.1±70.4%). This effect however was completely abolished in the presence of BAPTA. Though Ca2+ dependent, the translocation state of myocardial eNOS was not changed by the adenylate cyclase activator forskolin (0.3 μM) (+forskolin (t=5 min): -20.2±12.3%; n=3; p(0.05) nor was NO-release induced (n=2). Conclusions: 1) In human myocardium, BRL induced eNOS-translocation is dependent on intracellular Ca2+ whereas eNOS-phosphorylation is not. 2) At least in atrial myocardium, eNOS-translocation and not eNOS-phosphorylation generates bulk NO. 3) Though Ca2+ dependent, eNOS-translocation and NO-release could not be mimicked by adenylate cyclase activation as a mediator of β-adrenergic stimulation.